(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article describes the botanical characteristics, distribution, application in folk medicine, and healimg properties of the Zarpechak plant. In addition, information is provided about its ecological significance and beneficial effects on human health.